PENGARUH JENIS INSEKTISIDA TERHADAP HAMA POLONG Riptortus linearis F. (Hemiptera: Alydidae) DAN Etiella zinckenella Treit. (Lepidoptera: Pyralidae) PADA TANAMAN KEDELAI (Glycine max L.) - Yuswani Pangestiningsih; Desy Siburian; Lahmuddin Lubis (Jurnal Agroekoteknologi, 2014)
Desy siburian “The effect of various insecticide to the pest of pod Riptortus linearis F. (Hemiptera:Alydidae) and Etiella zinckenella Treit. (Lepidoptera: Pyralidae) towards soybeans (Glycine maxL.)” that supervised by Ir. Yuswani Pangestingsih, MS. and Ir. Lahmuddin Lubis, MP. Thisresearch was held in Desa Telaga Sari Kecamatan Tanjung Morawa Kabupaten Deli Serdang inJuly to September 2013. The method that used was non factorial “Completely Randomized BlockDesign” consist of 7 treatment and 3 repeatable. The treatment which tested were A0 (control), A1(Annona muricata seeds), A2 (Morinda citrifolia seeds), A3 (Jatropha curcas seeds), A4(chlorfiripos insecticide), A5 (agens Bacillus thurngiensis), and A6 (agens Beauveria bassiana).The parameter which were attack percentage of Riptortus linearis and Etiella zinckenella, thepopulation of nimfa Riptortus linearis and larva Etiella zinckenella, and also the production. Theresearch resulted that, the all of insecticide significantly effected the pest of pod Riptortus linearisand Etiella zinckenella. The best treatment to the Riptortus linearis is A2 (Morinda citrifolia seeds200 gr/l) that the lowest attack percentage (10.00%) and Etiella zinckenella is A4 (chlorfiriposinsecticide) that the lowest attack percentage (6,95).Keywords: Riptortus linearis, Etiella zinckenella, insecticide.